2017
DOI: 10.1371/journal.pone.0189537
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan coating as an antibacterial surface for biomedical applications

Abstract: Background and objectivesA current public health issue is preventing post-surgical complications by designing antibacterial implants. To achieve this goal, in this study we evaluated the antibacterial activity of an animal-free chitosan grafted onto a titanium alloy.MethodsAnimal-free chitosan binding on the substrate was performed by covalent link via a two-step process using TriEthoxySilylPropyl Succinic Anhydride (TESPSA) as the coupling agent. All grafting steps were studied and validated by means of X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 43 publications
1
32
0
1
Order By: Relevance
“…Despite the extensively described correlation between micro/nano-scale features and osseointegration, the implant failure induced by microbial adhesion and biofilm accumulation is still an open question [44]. It is proven that titanium surfaces do not prevent bacterial adhesion by themselves [45] and their coating, either physical or covalent, with antimicrobial actives is a thriving and challenging field of research [28].…”
Section: Titanium Functionalization and Prevention Of Bacteria Adhesionmentioning
confidence: 99%
“…Despite the extensively described correlation between micro/nano-scale features and osseointegration, the implant failure induced by microbial adhesion and biofilm accumulation is still an open question [44]. It is proven that titanium surfaces do not prevent bacterial adhesion by themselves [45] and their coating, either physical or covalent, with antimicrobial actives is a thriving and challenging field of research [28].…”
Section: Titanium Functionalization and Prevention Of Bacteria Adhesionmentioning
confidence: 99%
“…There was some research which showed that some polymers have some positive medical function, e.g., use as the sustained drug carrier material and promotion materials of wound healing [23], especially, sodium alginate (SA, 105 kDa, G/M (GulA/ManA) ratio = 0.85) and chitosan (MW: 134 kDa, degree of deacetylation: 96.44%) which have been used as advanced wound dressings in the clinic [24]. Also, some gel materials have an antibacterial activity such as chitosan [25,26]. The -NH 2 group of chitosan makes the nanogel show positive charge in the acid which can lead to negative bacterial cell membrane lysis via charge interaction [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both HA and CMCS are helpful for the adhesion and proliferation of human gingival fibroblasts. Chuan et al, 2015;Gao et al, 2017;Kabirian et al, 2019 Double bond-containing polymer Antifouling, antimicrobial, anti-fogging Contact lens Zhao et al, 2016;Kurowska et al, 2017 Polymer brush Antifouling, antimicrobial Glass, quartz, Ti Jie et al, 2015;Yu et al, 2015;Xu et al, 2017 Poly(NIPAAM) Antifouling, bactericidal Glass, PDMS, silicon Wang et al, 2016 PDA Antifouling, antimicrobial, antibacterial, antibiofilm Glass, stainless steel, plastic, gauze, catheter Liu andHuang, 2016;Su et al, 2016;Zhang et al, 2017;Zhou et al, 2017 Chitosan andderivatives Antibacterial, antibiofilm Ti, PU, PVF Li et al, 2017;D'Almeida et al, 2018;Yang M. et al, 2018 PHMB Broad-spectrum antimicrobial, bactericidal, antifouling, antibiofilm Silicone resin Su et al, 2017;Zhi et al, 2017 Responsive polymer brush Antifouling, antimicrobial, antibacterial Glass, Si, PU, MWCNTs, SiO 2 , Fe 3 O 4 Chen et al, 2010;Hu et al, 2013;Qu et al, 2015;Yan et al, 2016;Yaghoubi and Parsa, 2019 The Ti substrate was also modified by chitosan via coupling agent of triethoxysilylpropylsuccinic anhydride, and achieved the antibacterial effectiveness against E. coli and S. aureus (D'Almeida et al, 2018). Another example of chitosan-based coating on polyurethane (PU), polyvinyl fluoride (PVF) and Ti substrates was provided by Neoh group (Li et al, 2017).…”
Section: Covalent Graftingmentioning
confidence: 99%